PRINCIPAL COMPONENT ANALYSIS AND ESTIMATED BREEDING VALUES FOR SELECTING SUITABLE PARENTAL GENOTYPES IN RICE (ORYZA SATIVA L.) - Khatun, M. (Society for the Advancement of Breeding Research in Asia and Oceania, 2023)
Appropriate parental selection is the breeder’s main concern to exploit the highest genetic diversity and generate superior genotypes for subsequent breeding programs. Hence, the presented investigation proceeded to evaluate 353 breeding lines of rice at three breeding zones (Rajshahi, Cumilla, and Gazipur) in Bangladesh in replicated yield trials during the Boro season of 2018–2019 to identify the best genotypes and utilize them as parental materials. Data recorded on 12 yield-related traits helped to determine the best breeding lines with higher predicted breeding values. The first five principal components (PC1, PC2, PC3, PC4, and PC5) represented more than 70% (75.1%) contribution to the variability of the data. Three hundred fifty-three rice genotypes incurred distribution into five clusters over three environments. Clusters I, II, III, IV, and V comprised 66, 51, 83, 79, and 74 genotypes, respectively. Based on estimated breeding values (EBVs), IR107971-B-B RGA-B RGA-202 showed the highest value (0.395), followed by IR 108000-B-B-B-B-13 (0.329), IR 103309-B-B RGA-B RGA-194 (0.321), IR 107982-B-41-1-2-1 (0.291), IRRI 174 (0.264), and IR 107976-B-B RGA-B RGA-254 (0.234). The lowest EBV (0.022) appeared in IR103309-B-B RGA-B RGA- 204 among the top 20 genotypes. Both IR 103309-B-B RGA-B RGA-194 (0.321) and IR 107982-B-41- 1-2-1 (0.291) could benefit as parents for further breeding programs having higher EBVs and higher genetic diversity.